2021
DOI: 10.1080/1475939x.2021.2014947
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ experiences of ICT training in Nepal: how teachers in rural primary schools learn and make progress in their ability to use ICT in classrooms

Abstract: This article reports on teachers' experiences of ICT training in rural areas of Nepal. It discusses aspects of policy documents to help understand the Nepali educational context, before highlighting the challenges of establishing and maintaining infrastructure and professional learning opportunities across a country with challenging terrain and extreme environmental conditions. It then examines teachers' perceptions in five rural primary schools about their experiences of training to use modern educational tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 30 publications
(40 reference statements)
4
42
0
Order By: Relevance
“…They regarded it as an alternative mode of learning English from home in the absence of physical classroom learning. Studies (Rice et al, 2020;Wu & Gao, 2020;Rana et al, 2021) have demonstrated that it is important for teachers to have technological, pedagogical and content knowledge to implement ICT tools in multicultural and heterogeneous classrooms. Holland (2019) stressed that the trend towards autonomous learning makes it important for teachers to incorporate the use of online learning tools as preparation for the 21 st -century world.…”
Section: Discussionmentioning
confidence: 99%
“…They regarded it as an alternative mode of learning English from home in the absence of physical classroom learning. Studies (Rice et al, 2020;Wu & Gao, 2020;Rana et al, 2021) have demonstrated that it is important for teachers to have technological, pedagogical and content knowledge to implement ICT tools in multicultural and heterogeneous classrooms. Holland (2019) stressed that the trend towards autonomous learning makes it important for teachers to incorporate the use of online learning tools as preparation for the 21 st -century world.…”
Section: Discussionmentioning
confidence: 99%
“…It was evident from observations that teachers engaged students in the prescribed textbooks instead of following flipped learning strategies. Their replication of physical classroom pedagogies in online classes heavily depending on prescribed textbooks would have augmented what they used to do in the normal physical classroom ( Rana, 2018 ; Rana et al, 2018 ; Rana, 2022 ). It was evident from the participants’ comments that schools are unprepared to implement remote teaching.…”
Section: Discussion: Implication For Online Educationmentioning
confidence: 99%
“…It is essential to address ICT-related issues, such as the lack of ICT infrastructure in schools, teachers’ limited or no digital literacy and students’ lack of access to digital technology, to enhance the quality and efficiency of education in the context of Nepal ( Lim, 2007 ). Rana et al (2022) suggest developing a specific strategic plan, funding for ICT infrastructure and providing adequate ICT training for teachers to implement the education policy on ICT and transform traditional pedagogies to modern learning. Agyei’s (2020) study in African countries investigated that intensive ICT training enables teachers to effectively use ICT facilities and increases the sustainability of ICT practices in education.…”
Section: Access To Information and Communication Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the effects of ICT use in education on students were examined from a multidimensional perspective. In the literature, there are many studies on the use of ICT in education (Adam & Metljak, 2022;Guillén-Gámez & Mayorga-Fernández, 2020;Rana, Greenwood & Henderson, 2022;Putri, et al, 2020;Spiteri & Chang Rundgren, 2020;Zubković, Pahljina-Reinić & Kolić-Vehovec, 2022). On the other hand, no study has been found that examines the effects of ICT use in education on primary school students with a mixed method design.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%